MAUS-TRATOS CONTRA CRIANÇAS E ADOLESCENTES NO MUNICÍPIO DE SÃO BORJA-RS: DADOS DO CONSELHO TUTELAR E CONDUTA DOS PROFISSIONAIS DE SAÚDE - Soares, Maria do Carmo Fontella (2020)
Social Work is a profession of historical reference that permeates its actions in the fight for the guarantee of rights, based on its code of professional ethics, it operates in different institutional spaces, in the defense of working relationships with multiprofessional teams, always seeking their continued education. These professionals experiences, directly in his work practice and with his sensitive and welcoming look, issues of abuse against children and adolescents, which is a serious social problem that is perpetuated in our country. The mistreatment of children and adolescents is a real social wound, responsible for high rates of morbidity and mortality in this age group, requiring a serious and urgent response from society. Health Services cannot avoid dealing with this serious problem, which is part of Public Health, together with other government sectors. Any health professional who becomes aware of or suspects a situation of violation of the human rights of children and adolescents must inform the competent services, programs, and organization in the area of children and adolescents, as well as notify the Guardian Council and notify the coordination of the Epidemiological Surveillance Service of the municipality. Thus, the present study aimed to investigate the conduct and knowledge of health professionals in relation to cases of abuse against children and adolescents in the municipality of São Borja-RS, to assess the characteristics of complaints to the guardianship council for cases of treatment against children and adolescents and verify the conduct and knowledge of health professionals in relation to the identification and responsibility of reporting cases of abuse against children and adolescents. In the form of an interview, a questionnaire with open and closed questions was applied to 200 health professionals with higher degrees, from November 2019 to January 2020 in the municipality of São Borja, RS. All ethical and legal precepts were respected. The results demonstrated the difficulty of the professionals involved in identifying cases of abuse and in the notification process, ignorance of the procedures, and fear of notifying cases of abuse in children and adolescent. The study aims to encourage continuing education programs for professionals, the continued specialization of child and adolescent protection institutions and strengthened service networks, to provide adequate professional support, helping to reduce the degree of professional insecurity.